Proteolytic Activity in Meadow Soil after the Application of Phytohormones - Holik, Ladislav; Vranová, Valerie (Biomolecules, 2019)
Phytohormones, similar to soil enzymes, are synthesized and secreted into the soil environment by fungi and microorganisms. Phytohormones are involved in regulating microbial community activity in the rhizosphere. This paper examines how auxins, cytokinins, ethephon and chlorocholine chloride affect the activity of native soil proteases in the organo-mineral horizon of an alpine meadow. In the meadow habitat, native soil proteases were inhibited by auxins whereas the effect of cytokinins on these enzymes was not statistically significant. A similar inhibitory effect on the activity of proteases was shown for ethephon and chlorocholine chloride, both of which also inhibited the activity of native soil proteases in the alpine meadow soil. Overall, the inhibitory effect of phytohormones on the activity of native protease activity may affect plant nutrition by retarding the nitrogen cycle in the soil. This work contributes to our understanding of the influence of substances produced by the rhizosphere that can actively participate in the activity of soil microorganisms and consequently influence the soil nitrogen cycle.
Keywords: proteasy; Rhizobiaceae; cytokininy; Grassland; dusík; pastviny; kyseliny indoloctové; Plant Growth Regulators; chlormekvát; Indoleacetic Acids; Chlormequat; regulátory růstu rostlin; Peptide Hydrolases; Nitrogen; Plant Proteins; organofosforové sloučeniny; Organophosphorus Compounds; půdní mikrobiologie; rostlinné proteiny; Cytokinins; Soil Microbiology